New marked-driven qualifications in real estate sector - Hanna Szumińska (Edukacja Ustawiczna Dorosłych)
The author of the article analyses the processes in the area of qualifications in the sec-tor of real estate after entry into force the low of Integrated Qualification System from 22.12.2015. Responses to the question of how after 3 years from system connection formal education and non-formal education and informal education the trade looks like. In comparative perspective are introduced issues: qualifications system until now, authorization, legal bases, processes of incorporation of qualifications. The baseline is ordered real estate market. Functioning Sector Council competence in Real Estate Management, sector frame in real estate management and complete descriptions of full and partial qualifications from formal and non-formal as well as market qualifications included typically in the Integrated Qualification Registry.